2013
DOI: 10.1101/gr.151571.112
|View full text |Cite
|
Sign up to set email alerts
|

The transcription start site landscape of C. elegans

Abstract: More than half of Caenorhabditis elegans pre-mRNAs lose their original 59 ends in a process termed ''trans-splicing'' in which the RNA extending from the transcription start site (TSS) to the site of trans-splicing of the primary transcript, termed the ''outron,'' is replaced with a 22-nt spliced leader. This complicates the mapping of TSSs, leading to a lack of available TSS mapping data for these genes. We used growth at low temperature and nuclear isolation to enrich for transcripts still containing outrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 77 publications
(99 reference statements)
2
78
0
Order By: Relevance
“…This value is also similar to the amount observed (10.8%) in D. melanogaster (Hoskins et al 2011). Promoters with similarly long widths have also been observed in human, mouse (Carninci et al 2006), and, more recently, C. elegans (Saito et al 2013). The distribution of consensus promoter shapes (Figure 2A, inset) indicates that both broad and peaked transcription initiation patterns are observed at D. pulex promoters.…”
Section: Discussionsupporting
confidence: 70%
“…This value is also similar to the amount observed (10.8%) in D. melanogaster (Hoskins et al 2011). Promoters with similarly long widths have also been observed in human, mouse (Carninci et al 2006), and, more recently, C. elegans (Saito et al 2013). The distribution of consensus promoter shapes (Figure 2A, inset) indicates that both broad and peaked transcription initiation patterns are observed at D. pulex promoters.…”
Section: Discussionsupporting
confidence: 70%
“…1C; red arrow ). Close examination of TSS data from Saito et al 2013 revealed both dispersed low-level transcription along the 1879 bp elt-2 upstream region and a distinct peak of transcriptional activity at -482 bp (Fig S3). …”
Section: Resultsmentioning
confidence: 99%
“…The exact sequences and relative positions of the cis -regulatory motifs necessary for driving elt-2 expression have not been determined, nor are there apparent TATA box (GTATAWWAG) or Sp1 core promoter motifs in the immediate region upstream of the elt-2 transcriptional start site (TSS) (WormBase release WS220) (Harris et al, 2010; Saito et al, 2013)). Furthermore, we could not identify any sequence similarities to the known basal promoter fragment of the pes-10 gene.…”
Section: Introductionmentioning
confidence: 99%
“…147,148 Thus, although the TSS has been mapped for individual genes in C. elegans, 149 genomewide approaches for TSS identification have only recently been performed. 145,147,148,150 These recent results have, for the first time, allowed scientists to analyze the regulation of early steps of Pol II transcription on a global scale. CTD phosphorylation patterns in C. elegans are similar to other metazoans.…”
Section: Transcriptional Elongation Regulation In C Elegansmentioning
confidence: 99%
“…158 This result suggests that Pol II binding at these genes may reflect a paused or stalled polymerase that is regulated for expression later in development. 158 A separate analysis of Pol II ChIP data showed a 5′ peak of Pol II binding at both spliced and unspliced genes, 150 although this peak can be further downstream of the TSS (100-170 bp) than paused Pol II in Drosophila and mammals (25-60 bp). However, using the current gold standard for identification of Pol II pausing, genome-wide polymerase run-on sequencing (GRO-seq), Meyer and colleagues did not observe evidence of wide-spread Pol II pausing in worms under optimal growth conditions.…”
Section: Elegans Somatic Ser2-p Requires Cdk-9 and Cdk-12mentioning
confidence: 99%